(untitled) (Forum Agribisnis, 2022)
Private Forest is the forest located outside forest area and growing on land that is encumbered with land rights. Private forest have important role need to be maintained to support benefits for economic, social and ecological aspects. In addition to provide financial benefits, private forest have environmental services potential to reduce carbon dioxide (CO2). To strengthen business capital forestry in order rehabilitation of forest and land, the government form public services center for financing forest development (BLU Pusat P2H), Ministry of Environments and Forestry. This research aims to evaluate delaying timber harvesting loan in Wonogiri Regency, Central Java Province. The research was conducted from July 2020 to March 2021. Sampling by 182 respondents which consist of debitor farmers and non debitor farmers in Wonogiri Regency, Central Java Province. The research results show that the average income level of debitor farmers greater than the average income non debitor farmers. Private forest management activities are still done traditionally and simply. The level of financial feasibility was calculated by Revenue Cost Ratio (R/C Ratio) on the loan interest rate 7,5%. The study showed that R/C Ratio 1,79. Total population density in debitor farmers private forest was 19.561 tree was carbon stock trees contain 11.345,38 ton CO2, non debitor farmers forest was 13.003 tree was carbon stock trees contain 7.541,74 ton CO2. Evaluation with likert scale show that the implementing delaying timber harvesting loan in Wonogiri Regency about 72,442% it is mean good category. The results of the analysis showed that the process of service this loan has a weakness in long terms of the time period of submission and distribution of funds showed that the process of the submission of credit proposals debitor reached the stage of distribution of fund need range time six months then required increased acces services loan quickly .